Revision Total Knee Arthroplasty after Severe Notching of the Anterior Femoral Cortex - Kinney, Matthew C.; Kamath, Atul F.; Shah, Roshan P.; Israelite, Craig L. (The Journal of Knee Surgery, 2013)
Anterior femoral cortex notching is a known complication of total knee arthroplasty (TKA). In severe cases, notching may alter the mechanical properties of the distal femur. We report a patient with significant femoral notching and malpositioning of the femoral prosthesis after TKA, leading to unresolved postoperative pain, decreased range of motion, and functional disability. The severity of this lesion required the use of augments and an offset femoral stem for improved alignment during revision arthroplasty, which is described in this brief technical note.
Keywords: revision total knee arthroplasty; anterior femoral notching; augmentation; complications